2016
DOI: 10.1038/srep35258
|View full text |Cite
|
Sign up to set email alerts
|

High pressure die casting of Fe-based metallic glass

Abstract: Soft ferromagnetic Fe-based bulk metallic glass key-shaped specimens with a maximum and minimum width of 25.4 and 5 mm, respectively, were successfully produced using a high pressure die casting (HPDC) method, The influence of die material, alloy temperature and flow rate on the microstructure, thermal stability and soft ferromagnetic properties has been studied. The results suggest that a steel die in which the molten metal flows at low rate and high temperature can be used to produce completely glassy sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 64 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…As a vacuum forming method, EPV-HPDC offers a novel pathway for manufacturing other advanced materials, such as metallic glass matrix composites, high-entropy alloys, and nanostructured materials, in complex shapes. Furthermore, the flowing speed of the supercooled liquid and solidification pressure in the EPV-HPDC process can reach tens of meters per second and hundreds of megapascal [16], which are orders of magnitude larger than that of the common fabricating way of the BMGs, such as suction casting. Hence, the EPV-HPDC process provides access to study some of the critical scientific issues, such as the extreme fluid dynamics of glass forming liquid, shear-induced structural changes in fast-relaxing atomic liquids and melt [38,39], and relaxation kinetics of supercooled glass forming liquid under pressure [40], which are fundamental concerns for amorphous materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a vacuum forming method, EPV-HPDC offers a novel pathway for manufacturing other advanced materials, such as metallic glass matrix composites, high-entropy alloys, and nanostructured materials, in complex shapes. Furthermore, the flowing speed of the supercooled liquid and solidification pressure in the EPV-HPDC process can reach tens of meters per second and hundreds of megapascal [16], which are orders of magnitude larger than that of the common fabricating way of the BMGs, such as suction casting. Hence, the EPV-HPDC process provides access to study some of the critical scientific issues, such as the extreme fluid dynamics of glass forming liquid, shear-induced structural changes in fast-relaxing atomic liquids and melt [38,39], and relaxation kinetics of supercooled glass forming liquid under pressure [40], which are fundamental concerns for amorphous materials.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the HPDC process is also considered as the one of the methods with the most potential to be applied to the large-scale production of BMG components with sophisticated geometries. Recently, low oxygen affinity Fe-based bulk metallic glass with a key-shape was produced successfully using a traditional HPDC method in an open atmosphere [16]. However, most glass formers are extremely oxidizable, and thus are difficult to be synthesized directly by this route.…”
Section: Introductionmentioning
confidence: 99%
“…The binaries Ag-Pr, Be-Fe, Ag-Yb, Mg-Eu, Ag-Te and Ag-Sm are also proposed with confidence to form bulk metallic glasses. Of these, Ag-Pr has been suggested as a potential metallic glass former 15 and Fe, Ag and Te have been used as additions in multicomponent metallic glass systems in various combinations 45–47 , similar to Ag-Yb and Mg-Eu. Furthermore, nearly pure Ag-Te has been reported in some cases when investigating Te- based chalcogenide glasses 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich et al (2012) reported that Zr58.5Cu15.6Ni12.8Al10.3Nb2.8 BMG with size of 5mm can be prepared by a horizontal vacuum cold-chamber die casting process. Ramasamy et al 2016 found Fe-based bulk metallic glass key-shaped specimens can be fabricated by HPDC under Ar atmosphere. However, systematic study on the fabrication ability of HPDC for a certain composition is still absent.…”
Section: Introductionmentioning
confidence: 96%